“¡Aparición con vida!”: a importância da trajetória das Madres de Plaza de Mayo para os direitos humanos - Figueiredo, Marina [UNIFESP] (2015)
Over the years there has been a significant institutional and normative strengthening of the principles of human rights translated through Treaties and Conventions. This does not mean that these principles are promoted to social reality, since serious violations of human rights still linger around the world. So, there is a practical limit to bet only on institutional and regulatory aspects as a form of protection and promotion of human rights. Therefore, the challenge is to investigate other ways in which human rights can be an important emancipatory tool that promotes in practice, its own principles. The policies carried out by the dynamic social movement Mothers of Plaza de Mayo, in the context of the last dictatorship in Argentina, found alternative ways of doing politics able to promote human rights principles involving emancipative results in practice.